How to shape communication for CO2-derived insulation boards considering different accepter profiles - Lisanne Simons; Martina Ziefle; Katrin Arning (Environment, Development and Sustainability, 2023)
Climate change is a constant global challenge. An approach to help mitigate climate change is carbon capture and utilization (CCU), in which captured CO2 is reused as raw material for consumer products. Because innovations like CCU are unfamiliar to the general public, their communication is critical for a successful rollout. To date, sustainability innovation research has largely neglected the empirical study of communication. The present study contributes to studying the information and communication needs of laypeople based on perceptions and acceptance patterns for CCU by focusing on acceptance profiles for CCU-based insulation boards. In an empirical two-step approach, a qualitative interview prestudy was followed by a quantitative questionnaire measurement (N0.167em=0.167em643). Using k-means clustering, the respondents were divided into three acceptance groups: rejecters (15%), tentative accepters (51%), and strong accepters (34%). Analysis showed that regarding their demographics and personality traits, tentative accepters and rejecters were similar. All segments trusted science and health experts best, and only the rejecters distrusted some specific actors. Information on the product's risks and functional properties was most important for all acceptance groups. Based on the study's insights, both general and targeted managerial communication and policy guidelines were formulated.
Keywords: 330; Acceptance; Trust; Communication; Information; Carbon capture and utilization (CCU); Insulation boards